PENURUNAN SIFAT FISIK DAN SIFAT KIMIA BUAH APEL (Malus domestica) VARIETAS MANALAGI SELAMA PENYIMPANAN PADA SUHU RUANG DAN SUHU 5°C - , CHRIS NILA ANDRIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study is the effect of storage at low temperatures (5 ° C) and room temperature on postharvest quality of apples (Malus domestica) varieties manalagi, which is a fruit that is more and more consumed by the people of Indonesia. This study aims to 1) determine changes in physical and physiological properties (texture, weight loss, color and respiration rate) occurring in apple (Malus domestica) pascepanen at room temperature storage and low temperature (5 ° C) for 5 weeks. 2) Knowing the changes in the chemical properties (acidity, sugar content, and water content) that occurs in apples (Malus domestica) on postharvest storage at room temperature and low temperature (5 ° C) for 5 weeks. 3) Know the shelf life of apple (Malus domestica) varieties manalagi stored at room temperature and room temperature (5 ° C) during 5 weeks of storage. This study shows that the sugar acid ratio, decreased weight loss, water content, and increased respiration rate during storage. As for sugar, acidity, and texture decreased.Changes in physical properties and chemical properties of apple varieties manalagi stored at low temperature less than manalagi varieties of apples stored at room temperature. This study shows that the storage temperature is very influential to the quality of the apple varieties manalagi